Avaliação do infiltrado de macrófagos na parede arterial de pacientes com arterite de takayasu. - Santos, Joao Paulo Dos [UNIFESP] (2019)
Introduction – Takayasu's arteritis (TA) is a systemic vasculitis of unknown etiology that affects large arteries, such as the aorta and its main branches. The inflammatory infiltrate of the arterial wall consists of macrophages, multinucleated giant cells, natural killer (NK) cells, neutrophils and CD4+ T cells, CD8+ T cells and γδ T cells. No studies have evaluated macrophages phenotypes present in the inflammatory infiltrate of the arterial walls in patients with TA. Objective – The primary aim of this study was to evaluate which macrophage phenotype is predominant in the inflammatory infiltration in the aorta of patients with TA. Secondary study aims were to compare the frequency of macrophages, T cells, B cells and NK cells in the aorta from TA patients, patients with atherosclerotic disease (AD) and healthy controls (HC); to describe the predominant localization of macrophages in the aorta from TA patients; to analyze associations between infiltration of macrophages and T cells, B cells and NK cells in the arterial wall and clinical disease activity, histological disease activity, concomitant atherosclerotic lesions and prednisone use. Materials and Methods – We performed a cross-sectional study using immunohistochemistry to evaluate the expression of macrophages (CD68), T cells (CD3), B cells (CD20), NK cells (CD56), as well as M1 (CD86) and M2 (CD206) macrophages in inflammatory infiltration in the aorta from TA patients (n = 22), patients with AD of the aorta (n = 9) and HC (n = 8). Results – The thoracic aorta was assessed in 86.4% of TA patients, in 77.8% of patients with atherosclerotic disease and in 100% of controls. The abdominal aorta was evaluated in remainder. The surgical procedure was performed at the time of diagnosis in 54.5% of patients with TA. Clinical activity of the disease was observed in 54.5% of cases, histological activity in 40.9% and atherosclerotic lesions in 27.3% of patients with TA. Only 36.3% of the patients with TA were on glucocorticoid, immunosuppressive and/or biologic agents. The frequency of macrophages, M1 macrophages, T cells, B cells and NK cells was higher in the aorta from TA and AD patients compared with HC, but no differences were found among all groups for M2 macrophages. In TA, macrophages and T cells were the most abundant cells in the aorta while M2 macrophages were more frequently found than M1 macrophages. No differences were found concerning macrophages, T cells, Bcells or NK cells between TA patients presenting active disease and those in remission nor between TA patients with and without concomitant atherosclerotic lesions in the aorta. T cells were more frequent in the aorta of TA patients with active disease based on histological evaluation compared with those presenting chronic fibrotic lesions, but no differences were found in the expression of macrophage markers. The use of prednisone was associated with a significantly lower T cell count in the aorta of TA patients whereas no differences were observed for other cell markers. Conclusions – M2 macrophages are more frequently found in the aorta of TA patients than M1 macrophages. Macrophages and T cells are the most frequent cells in the inflammatory infiltrate in the aorta of TA patients. T cells were associated with histological disease activity and with prednisone use in TAK but not macrophages.